PEMERINTAH DAERAH DALAM SEKTOR PENDIDIKAN: (BANTUAN BEASISWA TERHADAP MASYARAKAT KURANG MAMPU DI KABUPATEN KUANTAN SINGINGI TAHUN 2013-2016) - Dahlena Dewi Fitri; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Scholarships are grants in the form of financial assistance provided to individuals, students or students who aim to be used for the sustainability of education pursued. The meaning of government management is a typical process consisting of acts of planning, organizing, mobilization and control are undertaken to determine and achieve the goals that have been determined. This study aims to determine the Roles and Obstacles of Local Government in the Education Sector: (scholarship assistance to poor people in Kuantan Singingi Regency Year 2013-2016).This research uses qualitative research method with descriptive research type, which can be interpreted as problem-solving process investigated by describing the circumstances of research subject based on facts that appear during the research which then continued with based on existing theories. Budget for scholarship assistance is less Capable of this is still decreased every budget, while in the role of government has not optimal because there is still a lot of cheating and aid is not right target due to many manipulation of data and game from unscrupulous government in choosing.The conclusion of this study states that the budget for scholarship aid for the underprivileged, especially for the education sector of university level students is still considered inadequate, this is because the amount of budget given by the local government is still fluctuating / decreasing in every budget year, the role of government based on The survey is known that in the distribution of scholarship aid is still found a lot of fraud and assistance that is not right target, especially in terms of supervision and selection of acceptance is still encountered some lack of much encountered data manipulation by the applicant as well as the game from the government itself who flew to vote on receiving assistance.Keywords: Role, Government Management, Beasiwa Help